AcuityView: An r package for portraying the effects of visual acuity on scenes observed by an animal. Issue 3 (29th October 2017) - Caves, Eleanor M.; Johnsen, Sönke
Abstract: Visual acuity is one of three basic parameters that characterize a visual system. However, few comparative studies of signals, camouflage and ecology in general have considered visual acuity. This is unfortunate, because humans have high acuity, and thus researchers may focus on visual details of animals and habitats that are not actually visible to the relevant species. Here we present AcuityView, a package for use in the software r which uses Fourier methods, measures of a viewer's acuity, viewing distance and the size of an image to modify images. AcuityView renders an image in a way that preserves only the information that an animal with a given visual acuity can detect at a certain distance, thus displaying an image that shows only the visual information available to that viewer. Ultimately, this will allow for a more informed analysis of what aspects of an animal's visual world may be detectable, and thus relevant to their ecology.